KOMPETENSI, LINGKUNGAN KERJA DAN KUALITAS PELAYANAN - Hadi, Larbiel; Andri, Seno; Rusli, Zaili (Jurnal Ilmu Administrasi Negara, 2019)
Competence, Work Environment and Service Quality. This study aims to determine and analyze the influence of competence, work environment together and partially on the quality of service at the Faculty of Economics and Social Sciences UIN Suska Riau. This type of research is a quantitative approach with survey methods and data analysis is quantitative / statistical. The announcement of primary data through a questionnaire on 98 employee respondents at the Faculty of Economics and Social Sciences UIN Suska Riau as well as secondary data through organizational data relating to the problem under study. Data analysis method uses Multiple Linear Regression with the help of SPSS application. The results showed that together the variables of competence, work environment significantly influence the service quality of employees with f count (77.949)> f table (3.09) and the contribution coefficient of determination (R2) is 62.1%. 37.1% is influenced by other variables not examined in this study.